Taksiran Level Tabel Kematian dengan Metode Trussell pada Populasi Tertutup - Yayat Karyana (Program Studi Statistika Unisba, 2005)
Many methods for estimation level of Life Tabele. One if is Trussel Method. This method canbe used for open population. If no migration effect it can be used in close population too. It based ondeath probability value at age x, as Q(x)’ = k(i) D(i,)’, where: k(i) = a(i) + b(i) P(1)/P(2) + c(i) P(2)/P(3) ,a(i), b(i) and c(i) multiplier of Trussel, D(i) is proportion of children dead by women in age group i andP(i) is average of parity per women in ege group i. In this paper will estimate level of Life Table of WestJava and Banten whit assumtion open and closed population.